background image

18.2. ON PSEUDOFUNCOIDS

283

so

h

f

i

i

X

=

d

X

up

X

h

f

i

i

X

.

18.2. On pseudofuncoids

Definition

1455

.

Pseudofuncoid

from a set

A

to a set

B

is a relation

f

between

filters on

A

and

B

such that:

¬

(

I f

0)

,

I t J

f

K ⇔ I

f

K ∨ J

f

K

(for every

I

,

J ∈

F

(

A

),

K ∈

F

(

B

))

,

¬

(0

f I

)

,

K

f

I t J ⇔ K

f

I ∨ K

f

J

(for every

I

,

J ∈

F

(

B

),

K ∈

F

(

A

))

.

Obvious

1456

.

Pseudofuncoid is just a staroid of the form (

F

(

A

);

F

(

B

)).

Obvious

1457

.

[

f

] is a pseudofuncoid for every funcoid

f

.

Example

1458

.

If

A

and

B

are infinite sets, then there exist two different

pseudofuncoids

f

and

g

from

A

to

B

such that

f

(

P

×

P

) =

g

(

P

×

P

) =

[

c

]

(

P

×

P

) for some funcoid

c

.

Remark

1459

.

Considering a pseudofuncoid

f

as a staroid, we get

f

(

P

×

P

) =

f

.

Proof.

Take

f

=

(

X

;

Y

)

X ∈

F

(

A

)

,

Y ∈

F

(

B

)

,

T

X

and

T

Y

are infinite

and

g

=

f

(

X

;

Y

)

X ∈

F

(

A

)

,

Y ∈

F

(

B

)

,

X w

a,

Y w

b

where

a

and

b

are nontrivial ultrafilters on

A

and

B

correspondingly,

c

is the funcoid

defined by the relation

[

c

]

=

δ

=

(

X

;

Y

)

X

P

A, Y

P

B, X

and

Y

are infinite

.

First prove that

f

is a pseudofuncoid. The formulas

¬

(

I f

) and

¬

(

f I

) are

obvious. We have

I t J

f

K ⇔

\

(

I t J

) and

\

Y

are infinite

\

I ∪

\

J

and

\

Y

are infinite

\

I

or

\

J

is infinite

\

Y

is infinite

\

I

and

\

Y

are infinite

\

J

and

\

Y

are infinite

I

f

K ∨ J

f

K

.

Similarly

K

f

I t J ⇔ K

f

I ∨ K

f

J

. So

f

is a pseudofuncoid.

Let now prove that

g

is a pseudofuncoid. The formulas

¬

(

I g

) and

¬

(

g I

)

are obvious. Let

I t J

g

K

. Then either

I t J

f

K

and then

I t J

g

K

or

I t J w

a

and then

I w

a

∨ J w

a

thus having

I

g

K ∨ J

g

K

. So

I t J

g

K ⇒ I

g

K ∨ J

g

K

.

The reverse implication is obvious. We have

I t J

g

K ⇔ I

g

K ∨ J

g

K

and

similarly

K

g

I t J ⇔ K

g

I ∨ K

g

J

. So

g

is a pseudofuncoid.

Obviously

f

6

=

g

(

a g b

but not

a f b

).

It remains to prove

f

(

P

×

P

) =

g

(

P

×

P

) = [

c

]

(

P

×

P

). Really,

f

(

P

×

P

) = [

c

]

(

P

×

P

) is obvious. If (

A

X

;

B

Y

)

g

(

P

×

P

) then either

(

A

X

;

B

Y

)

f

(

P

×

P

) or

X

up

a

,

Y

up

b

, so

X

and

Y

are infinite and

thus (

A

X

;

B

Y

)

f

(

P

×

P

). So

g

(

P

×

P

) =

f

(

P

×

P

).

Remark

1460

.

The above counter-example shows that pseudofuncoids (and

more generally, any staroids on filters) are “second class” objects, they are not

full-fledged because they don’t bijectively correspond to funcoids and the elegant

funcoids theory does not apply to them.